What is Knowledge Management and How it Benefits Your Department - Kris Helge (Academic Chairpersons Conference Proceedings, 2022)
Presenter and participants will define knowledge management (KM). They will also discuss emerging strategies and best practices regarding KM that benefit an academic department, and examine how effective KM systems help traverse unpredictable challenges such as COVID-19. Additionally, they scrutinize how to preserve, pass along, and securely store vital data, information, and knowledge; and how KM prevents information silos, and information loss.
Keywords: knowledge management information preservation access